TH3.1: Analysis of Dietary Diversity and Determinants of Fish Consumption among Women, Children and Households in Bangladesh - Njogu, Lucy (WorldFish, 2022)
Malnutrition in Bangladesh is still a challenge, especially among women and children, partly due to low dietary diversity and discrimination in intra-household food allocation. Given the high levels of malnutrition in Bangladesh, and the importance of fish in providing micro-nutrients, we sought to understand the dietary diversity levels, patterns and fish consumption determinants in households, and among women and children. We collected data from 2669 households in Rangpur and Rajshahi divisions. The study employs a Household Dietary Diversity (HDD), Individual Dietary Diversity – Women (IDD-W) and Minimum Dietary Diversity (MDD) to analyze the diversity of diets in general households, among women and children, respectively. Results indicate that although the average HDD was relatively high (8.22), the mean IDD _W for women and children was much lower at 4.99 and 4.90, respectively. Dietary diversity scores increased with consumption of fish and number of fish species consumed. Intra-household discrimination and substitution of fish and other types of meat in the households, was evident from the results. Households consumed an average of two species and the most commonly consumed fish species were not necessarily the most affordable. Increase in level of education and pond ownership were among the factors that were found to increase fish consumption. Counterintuitively, distance to the market and the price of fish were found to increase fish consumption. We recommend promotion of policies that encourage consumption of nutritious foods; such as fish, among women and children. In addition, we recommend that development organizations consider tastes and preferences in implementing fish related projects.